Characterization of Insulin and Glucagon Genes and Their Producing Endocrine Cells From Pygmy Sperm Whale (Kogia breviceps) - Zhao, Liyuan; Wang, Likun; Aierken, Reyilamu; Wang, Wei; Wang, Xianyan; Li, Mingyu (Frontiers in Endocrinology, 2020)
Insulin and glucagon are two kinds of hormones secreted by pancreatic β and α cells, which regulate the glucose homeostasis together. The disorder of these two hormones will result in hyperglycemia or hypoglycemia. To better understand the endocrine physiology of cetaceans, we cloned and characterized the insulin and glucagon genes from pygmy sperm whale (Kogia breviceps). We obtained the complete coding sequences of the preproinsulin and preproglucagon genes, which encoding preproinsulin protein of 110 amino acid (aa) residues and encoding preproglucagon protein of 179 aa residues respectively. Sequence comparison, phylogenetic analyses, and synteny analyses indicated that their protein structures were similar to other mammalian orthologs. Moreover, we performed immunohistochemistry and immunofluorescence staining using insulin, glucagon and somatostatin antibodies for analysis of pygmy sperm whale islet distribution, architecture and composition. Our results showed the pygmy sperm whale islet was irregularly shaped and randomly distributed in the pancreas. The architecture of α, β and δ cells of the pygmy sperm whale was similar to that of adult pig. This is the first report about insulin and glucagon genes in cetaceans, which provided new information about the structural conservation of the insulin and glucagon genes, and new information on the properties of endocrine cells in cetacean for further studies.